Optical properties of alpha-zinc aluminum sulfide:chromium single crystals. - Broussell, Isabelle. (University of Ottawa (Canada), 1998)
The optical properties of the chromium doped spinel type semiconductor $\alpha$-$\rm ZnAl\sb2S\sb4$ have been examined over the temperature range 2-540K. From extrinsic absorption and photoluminescence spectra the transitions between the ground state $\rm\sp4A\sb{2g}$ and the excited levels $\rm\sp2E\sb{g}\ (R\sb1$ and R$\rm\sb2),\ \sp2T\sb{2g},\ \sp4T\sb{2g}$ and $\rm\sp4T\sb{1g}$ of the Cr$\sp{3+}$ ions were observed. A fit of the measured temperature dependence of the PL decay, using a four level model, yielded the lifetimes of the $\rm\sp2E\sb{g}\ (R\sb1$ and R$\sb2)$ and $\rm\sp4T\sb{2g}$ levels and the energy gaps between the $\rm\sp2E\sb{g}\sp{(1)}$-$\rm\sp2E\sb{g}\sp{(2)}$ and $\rm\sp2E\sb{g}\sp{(1)}$-$\rm\sp4T\sb{2g}$ states which were found to be very close to the values obtained from steady-state measurements. A configurational coordinate diagram for Cr$\sp{3+}$ ions in a $\alpha$-$\rm ZnAl\sb2S\sb4$:Cr spinel host has been constructed. Optical gain measurements at 198 K, 298 K and 380 K displayed two separate spectral regions associated to the Cr$\sp{3+}$ ions and possibly to Cr$\sp{4+}$ impurity centers. Gain values of up to 25 cm$\sp{-1}$ (730 nm) at 198 K were obtained. Finally the intrinsic photoluminescence measurements revealed an intense UV peak around 380 nm from 20 K to 296 K which corresponds to the indirect band gap of the host crystal, $\alpha$-$\rm ZnAl\sb2S\sb4.$
Keywords: Physics, Condensed Matter.